Review of stone columns, piled raft foundations, and combined stone columns and piles under raft as a ground improvement techniques for soft clay soils - Danish, Ahmed; Siti Noor Linda, Taib; Tahar, Ayadat; Alsidqi, Hasan; Muhammad, Ajmal (Materials Research Forum LLC, 2025)
This review paper aims to provide an in-depth analysis of three commonly used foundation systems: stone columns, piled raft foundations, and combined stone columns and piles under raft. These foundation techniques have gained significant attention due to their effectiveness in improving soil conditions and enhancing the load-bearing capacity of weak or problematic soils. The aim is to evaluate their effectiveness in addressing the challenges associated with building on soft clay. The review incorporates published research and case studies to compare the performance of each method in terms of enhancing bearing capacity, reducing settlement, and improving overall performance. The findings suggest that while each approach offers distinct advantages, the hybrid solution of combining stone columns and piles beneath a raft foundation offers the most comprehensive benefits for supporting structures on soft clay sites.